Black White Colour Bias among Young Malaysian Chinese Children - Rahman, Putri Zabariah; Wong, Su Luan (1986)
Previous studies of preschool children in the United States, Western Europe and Eastern Asia have demonstrated a bias favouring the colour white relative to the colour black. In this study, the Colour l.1eaning Test II was administered to urban Malaysian Chinese preschoolers, aged 5 and 6 years. The mean Colour Meaning Test II score of 18.33 indicated a definite pro-white/anti-black bias. The sex and age of the child was found to have no significant effect on the test score, The high level of bias favouring the colour white relative to the colour black suggest that the bias is universal and that strong influences have brought about this high level of bias. These children have no direct contact. with dark-skinned (black) and light-skinned (white) persons and do not live in II society in which there is a great socio-economic chasm between black and white races, but they are familiar with the concept of races as it relates to black-white skin colour and the designation of persons by colour names through watching television. This study lends support to the main causal factors that have been suggested for colour bias, which are cultural symbolism, mass media, literature and early diurnal experience